Setting the balance: Using biofeedback and neurofeedback with gymnasts - Shaw, L.; Zaichkowsky, L.; Wilson, V. (Journal of Clinical Sport Psychology, 2012)
The present paper evaluated the efficacy of a biofeedback/neurofeedback training program to create an optimal preperformance state to improve gymnasts` balance beam performance in competition. Training to increase heart rate variability (HRV) and sensorimotor rhythm while inhibiting theta was provided to 11 Division I gymnasts in 10 15-min sessions. Results of this uncontrolled study indicated that competition scores and scores from an independently judged video assessment improved throughout the training, beta decreased from preto postassessment, and there were no changes in HRV, sensorimotor rhythm, or theta. The withdrawal of training resulted in a decline of competition scores.